Tick-transmitted diseases. Part II. Pathogens Borrelia burgdorferi, Anaplasma phagocytophilum, Babesia microti - Wójcik-Fatla, Angelina; Szymańska, Jolanta; Buczek, Alicja (Polish Journal of Public Health, 2009)
Ixodes ricinus ticks are a reservoir and vector for numerous viruses, bacteria and protozoa, including species of medical and epidemiological significance. The bacteria Borrelia burgdorferi and Anaplasma phagocytophilum as well as the protozoa Babesia microti are among the pathogenic microorganisms transmitted by Ixodes ricinus ticks. The mentioned pathogens are etiological factors of tick-borne diseases that constitute an important public health problem: diagnostic, clinical and prophylactic. This concerns the most frequently occurring borreliosis which has many forms and multi-organ symptoms, the less frequent anaplasmosis with a non-characteristic clinical picture, and babesiosis – with the clinical picture similar to that of malaria. However, due to co-infections of Ixodes ricinus ticks with the pathogens: Borrelia burgdorferi, Anaplasma phagocytophilum and Babesia microti, mixed infections are possible. In the case of co-infection with the mentioned pathogens, patients may experience a mosaic of symptoms and a more severe course of disease. The paper presents the current knowledge on epidemiology and pathogenicity of Borrelia burgdorferi, Anaplasma phagocytophilum and Babesia microti. It also describes methods used in diagnostics of tick-borne diseases to detect infections with this pathogens: both in ticks and in humans.